Evolution characteristics of dynamic balance disorder over the course of PD and relationship with dopamine depletion - Gan, Jing; Wu, Xiaodong; Wan, Ying; Zhao, Jiahao; Song, Lu; Wu, Na; Wang, Hui; Yin, Yafu; Liu, Zhenguo (Frontiers in Aging Neuroscience, 2023)
Objective: To assess the evolution of the dynamic balance impairment over the course of Parkinson’s disease (PD) and clarify the contribution of striatal dopaminergic innervation to poor dynamic balance. Methods: 89 PD patients (divided to 2 groups according to H-Y stage) and 39 controls were included in our study. Kinematic data was recorded by a portable Inertial Measurement Unit system. Dopaminergic loss in striatal subregion was verified through 11C-CFT PET examination. The severity of white matter hyperintensities (WMHs) were assessed by Scheltens scale. The correlation between dynamic kinematic parameters and dopamine transporter availability were analyzed by multivariate regression analysis. Results: Early PD patients presented imbalance featured by smaller three-dimensional trunk ROM with reduced trunk coronal angular velocity during walking and reduced trunk sagittal angular velocity when stand-to-sit task (all p<0.05). These abnormalities were not more severe at later stage. The ROM in coronal and transverse planes during walking correlated with caudate DAT uptake (β=0.832, p=0.006, Q=0.030 and β=0.890, p=0.003, Q=0.030) after controlling the age, gender and WMHs. As the disease progressed, the trunk sagittal and transverse angular velocity during walking, trunk sagittal angular velocity when turning and sit-to-stand were obviously slower, accompany with reduced gait velocity gradually (all p<0.05). These parameters related to disease progression have no association with striatal DAT uptake (all p>0.05). Conclusion: The dynamic balance in PD was impaired from the early stage and the characteristics of the impairment changed differently as the disease progressed. Less contribution of dopaminergic denervation to PD dynamic balance disorders.